ANALIZING ACADEMIC PROKRASTINATION CAUSING FACTORS IN DESIGNING THESIS OF ATHLETE STUDENTS - Soegiyanto Soegiyanto; Ipang Setiawan; Moch Fahmi Abdulaziz; Dhimas Bagus Dharmawan; Vivi Septiana Parista (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran)
This study was aimed at identifying the factors that caused students of the athletes of the Faculty of Sport Sciences, Semarang State University (UNNES) to carry out procrastination actions in the preparation of the thesis and create a measure of academic procrastination in the preparation of thesis. This study used a mixed method with a sequential exploratory design. The population in this study were the students of Faculty of Sport Sciences, 2010, 2011 and 2012 UNNES who were preparing a thesis. The sampling method used was purposive random sampling. The qualitative data were gathered using questionnaires and interviews, while for quantitative data using the scale of academic procrastination made by the researchers themselves based on the results of qualitative data analysis. Qualitative data analysis technique used was interactive models while Lisrel item analysis was used to analyze quantitative data to confirm which factors had an influence on academic procrastination. The results show that 3 factors causing procrastination namely physical, psychological, and environmental factors. The factors that have the highest influence on academic procrastination are psychic aspects, namely internal factors in each athlete. ANALISIS FAKTOR PENYEBAB PROKRASTINASI AKADEMIK DALAM PENYUSUNAN SKRIPSI PADA MAHASISWA ATLET